1989
DOI: 10.1002/jsfa.2740470102
|View full text |Cite
|
Sign up to set email alerts
|

Loss of nitrogen through ammonia volatilisation during and following the application of pig or cattle slurry to grassland

Abstract: A BS T R A C TThe micrometeorological mass balance method \<*as used to determine ammonia (NH,)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(58 citation statements)
references
References 14 publications
7
51
0
Order By: Relevance
“…Such a course with the main part of emissions occurring in the first ten to twenty hours is quite common after slurry spreading and has often been documented (e.g. Pain et al, 1989;Mannheim et al, 1995;Braschkat et al, 1997;Génermont et al, 1998;Menzi et al, 1998;Misselbrook et al, 2002;Huijsmans et al, 2003;Rochette et al, 2008;Sanz et al, 2010). The conditions at the Oensingen grassland revert back to a small, potentially bi-directional flux regime after about 5 days and even the canopy compensation point returns to prefertilisation levels after about 10 days .…”
Section: Dynamics Of Nh 3 Volatilisationmentioning
confidence: 87%
See 1 more Smart Citation
“…Such a course with the main part of emissions occurring in the first ten to twenty hours is quite common after slurry spreading and has often been documented (e.g. Pain et al, 1989;Mannheim et al, 1995;Braschkat et al, 1997;Génermont et al, 1998;Menzi et al, 1998;Misselbrook et al, 2002;Huijsmans et al, 2003;Rochette et al, 2008;Sanz et al, 2010). The conditions at the Oensingen grassland revert back to a small, potentially bi-directional flux regime after about 5 days and even the canopy compensation point returns to prefertilisation levels after about 10 days .…”
Section: Dynamics Of Nh 3 Volatilisationmentioning
confidence: 87%
“…It comprises values between 4 % to almost 100 % (e.g. Pain et al, 1989;Braschkat et al, 1997;Génermont et al, 1998;Menzi et al, 1998;Huijsmans et al, 2001;Søgaard et al, 2002;Huijsmans et al, 2003;Misselbrook et al, 2002Misselbrook et al, , 2005aSanz et al, 2010;Spirig et al, 2010;Uusi-Kämppä and Mattila, 2010). The strong stickiness of the polar NH 3 molecule complicates measurements of ambient NH 3 concentrations (Parrish and Fehsenfeld, 2000;von Bobrutzki et al, 2010) and consequently fluxes.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, ammonia volatilization from animal husbandries has been assessed by micrometeorological mass balance methods [6,32] and by wind tunnels [23,38]. The in vitro model described in the present work had the advantage to be more simple, fast and cost-effective than both micrometeorological techniques and wind tunnels.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Kitai and Arakawa [19] suggested the sterilization of excreta from broiler chickens or the incubation of fresh excreta with the antibiotic thiopeptin. Ammonia release can be also prevented by slurry acidification [15,25,27,28,32,43]. For example, Stevens et al [41] reported that at least 80% of the ammonia release from pig and cow slurries could be prevented by acidifying the slurry to pH 6.0 and 5.5, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The quantity of this immediately available N can be almost half of the total N and this percentage is higher than that of the solid cattle manure (Beauchamp, 1986;Bechini & Marino, 2009;Sutton et al, 1986). A significant amount of the ammoniacal N in LCM can be lost, as NH 3 by volatilization, shortly after LCM application to soils (Beauchamp et al, 1982;de Jonge et al, 2004;Pain et al, 1989;Pfluke et al, 2011aPfluke et al, , 2011bWebb et al, 2010). However, this depends on the properties of the LCM and soil, where manure is applied, and also on the rate, manner, timing of application and weather conditions and interactions among these factors (Beauchamp et al, 1982;Mannheim et al, 1995;Pain et al, 1990;Reijs et al, 2007;Rochette et al, 2006;Sorensen, 1998;Thompson et al, 1990aThompson et al, , 1990b.…”
Section: Introductionmentioning
confidence: 99%